第52次日本南極地域観測隊気象部門報告2011 - 久光, 純司; ヒサミツ, ジュンジ; 小栗, 秀之; オグリ, ヒデユキ; 高野, 松美; タカノ, マツミ; 杉山, 暢昌; スギヤマ, ノブマサ; 山本, 敦; ヤマモト, アツシ; Hisamitsu, Junji; Oguri, Hideyuki; et al. (国立極地研究所, 2016)
この報告は第52次南極地域観測隊気象部門が，2011年2月1日から2012年1月31日まで昭和基地において行った気象観測結果をまとめたものである．観測方法，測器，統計方法等は第51次隊とほぼ同様である．越冬期間中の特徴のある気象状況は次のものがあげられる． 1）越冬期間中の雪日数は，210日と平年並み（平年値：200日）であるが，2011年2月から5月及び2011年12月から2012年1月の月最深積雪（各月で最も積もった雪の深さ）の順位は1位となり極値を更新した．6月から11月は順位が2位となり記録を更新した．降雪の深さ（積雪差）の月合計においては越冬期間中の半分の月で1位となり記録を更新した． 2）越冬期間中のブリザードの発生回数は30回と平年より多く，毎月ブリザードが発生した． 3）昭和基地上空のオゾン全量は，8月中旬から12月中旬までオゾンホールの目安となる220m atm-cm をほぼ継続して下回り，9 月21日には2011年の最小値である149m atm-cm（単位については4.2.1参照）を記録した． This report describes the results of meteorological observations at Syowa Station from February 1, 2011 to January 31, 2012, carried out by the Meteorological Observation Team of the 52nd Japanese Antarctic Research Expedition (JARE-52). The observation methods, instruments and statistical methods used by JARE-52 were almost the same as those used by the JARE-51. Remarkable weather phenomena observed during the period of JARE-52 are as follows: 1)JARE-52 experienced heavy snowfall with record-breaking maximum snow depth of the month from February 2011 to May 2011 as well as from December 2011 to January 2012. From June to November 2011, it placed the second in the past record of each month. Total amount of daily snow depth also hit the record high for half of the months during the wintering period. 2)The number of occurrences of the blizzard was 30 times, which was slightly larger than average year. But blizzard occurred every month during winter period. 3)The amount of total ozone over Syowa Station from mid-August to mid-December was continuously less than 220 m atm-cm used as a target for the ozone hole for most of this period. The value for September 21 was 149 m atm-cm, which marked the minimum value of year 2011. departmental bulletin paper